Blood SC5b-9 complement levels increase at parturition during term and preterm labor. (June 2015) - Segura-Cervantes, Enrique; Mancilla-Ramirez, Javier; Zurita, Luis; Paredes, Yuriria; Arredondo, José Luis; Galindo-Sevilla, Norma
Highlights: Complement is an effector of the native immune system associated with delivery. It is not known what the active complement is doing during parturition. Complement deposits are seen in fetal membranes at term parturition. Abstract: We explored the hypothesis that complement, an innate and adaptive immune effector, is active in the plasma of parturient women and is deposited on fetal membranes collected after delivery. A cross-sectional study was designed to evaluate complement activity at parturition. Pregnant women ( n  = 97) between 15 and 41 years of age were enrolled in a hospital protocol during the perinatal period to assess both SC5b-9 complement activity in blood and complement deposition on fetal membranes during parturition. Soluble SC5b-9 complement activity in plasma fractions was measured using a standard enzyme-linked immunosorbent assay (ELISA) that included specific anti-complement antibodies. Complement deposition on membranes was analyzed using immuno-dot blots and immunohistochemistry. Soluble SC5b-9 complement complex levels were increased in the plasma of women during term labor (TL; median 3361; range 1726–5670 ng/mL), preterm labor (PL; median 2958; range 1552–7092 ng/mL), and preterm premature rupture of membranes (PPROM; median 2272; range 167–6540 ng/mL) compared with pregnant women who were not in labor (P; median 1384; range 174–4570 ng/mL; P  < 0.001, Kruskal–Wallis test). Active complement, as assessed by the C9 neo-antigen in C5b-9 complexes, was deposited on fetal membranes, with no difference between term and preterm delivery. The deposition of active complement on fetal membranes was confirmed by immunohistochemistry. Women who underwent non-labor-indicated Cesarean sections did not exhibit complement deposition. Soluble SC5b-9 complement complex levels increased in the plasma of women during parturition, and complement C5b-9 complexes were deposited on fetal membranes.